Impact Of Socio-Economic Attributes On The Living Standards Of Females In Farming System Of Punjab, Pakistan - Ullah, TI; Anwer, HN; Musa, M; Sher, F (SAARC Journal of Agriculture, 2020)
In the context of farming, Punjab is bestowed with fertile land. It is a land of five rivers and friendly atmosphere for agriculture as well as for livestock. Majority of its population lives in rural areas and its major source of income is based on agriculture. Women are contributing a significant share in the field of farming. This study was carried out to investigate the effects of socio-economic factors on the living conditions of those women who are involved in any farming activities. The nature of study was quantitative. 400 women were selected through multiple sampling techniques from three different geographical zones of Punjab. The tool for data collection was interview schedule. Statistical Package of Social Science (SPSS) was used for quantitative analysis for enhancing the scope and validity of research. Bi-variate analysis was carried out for showing the relationship between variables. The study revealed positive as well as negative impacts on living conditions of women in this sector. This study shed a light on women participation as a farmer and its impact on their lives. The major suggestions were made after conducting the research that there should be proper training for women in agriculture sector. Proper health and education facilities should be provided to them and their children. Government should make policies to facilitate the women in farming system. SAARC J. Agri., 17(2): 53-66 (2019)